Persepsi masyarakat terhadap bantuan pemerintah melalui program penanggulangan kemiskinan perkotaan (P2KP) di Kota Gorontalo - ADAM, Helmi ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The research regarding the Society Perception on the Government Assistances given through Urban Poverty Alleviation Program at Gorontalo Town is aimed at three things: P2KP programs in 2007. This research counting the amount of the sharring budget that provided by Gorontalo government, and at indentifiying the supporting activities given to the P2KP Programs. This research uses qualitatif deskriptive methods. The data used in the research were classified into primary and secondary data. The primary data were gathered throught interview, questionnaires, and observation. Interview was conducted to the board BKM as well as to the prominent leaders in Gorontalo town, while questionnaries were given to 30 local government employees uses purposive and snowball sampling. The secondary data, on the other hand, were collected from several government and private institutions that closely related to the programs implementation. The result show that the majority of the society in Gorontalo (80 persen) are optimistic about the government assistances because the programs can increas the income of the people and decrease the poverty level at Gorontalo town. It found that 83 persen of the respondents said that the P2KP has plausible programs objectives as reflected from is economic, social, environment, and the housing programs. About 70 persen of the respondents mentioned that the success of the P2KP programs can not be separated from its qualified human resources who are capable, reliable, and thrustworthy. It is revealed from the research that the amount of the sharring budget given by local government in 2007 was Rp2.000.000.000,- (two millions rupiah) and by the local society was Rp336.707.848,- ( three hundreds thirty-six millions seven hundred seven thousand eight hundred forty-eight rupiah). Key words: Society Perception, Government assistances, P2KP